(untitled) (Periphērica, 2023)
Ambrosio Echemendía was an enslaved poet born in Cuba in 1843 and freed in 1865 thanks to a collection organized by white intellectuals. This article analyzes the importance of the press in this process. It focuses on the newspaper El Siglo, published in Havana, which reproduced articles from other newspapers such as El Fomento and El Telégrafo de Cienfuegos to call on subscribers to free the poet. The article highlights that this liberation process was made possible by the development of communications in Cuba, which from the 1830s had began to expand and create what Benedict Anderson called an “imagined community” of intellectuals who read the same news and act as a united group to promote a cause of social improvement.